1986
DOI: 10.1017/s0021900200111763
|View full text |Cite
|
Sign up to set email alerts
|

Bisexual Galton–Watson branching processes with superadditive mating functions

Abstract: For a bisexual Galton–Watson branching process with superadditive mating function there is a simple criterion for determining whether or not the process becomes extinct with probability 1, namely, that the asymptotic growth rate r should not exceed 1. When extinction is not certain (equivalently, r > 1), simple upper and lower bounds are established for the extinction probabilities. An example suggests that in the critical case that r = 1, some condition like superadditivity is essential for ultimate ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 10 publications
1
29
0
Order By: Relevance
“…In his original paper, Daley (1968) gave necessary and sufficient conditions for parasite extinction, for a model having several alternative mating functions and an arbitrary distribution for the number of offspring; in our special case, these reduce to µ ≤ 1 . These results were later extended (Daley et al, 1986) to the class of superadditive mating functions. Some numerical calculations were presented that appeared to indicate, for promiscuous mating (the pbGWp) and a Poisson distribution of offspring number, that the probability of extinction relative to that for the corresponding ordinary (asexual) Galton-Watson process, tends to a limit as the initial number (i) of parasites increases.…”
Section: Definition Of Modelmentioning
confidence: 85%
See 2 more Smart Citations
“…In his original paper, Daley (1968) gave necessary and sufficient conditions for parasite extinction, for a model having several alternative mating functions and an arbitrary distribution for the number of offspring; in our special case, these reduce to µ ≤ 1 . These results were later extended (Daley et al, 1986) to the class of superadditive mating functions. Some numerical calculations were presented that appeared to indicate, for promiscuous mating (the pbGWp) and a Poisson distribution of offspring number, that the probability of extinction relative to that for the corresponding ordinary (asexual) Galton-Watson process, tends to a limit as the initial number (i) of parasites increases.…”
Section: Definition Of Modelmentioning
confidence: 85%
“…Some numerical calculations were presented that appeared to indicate, for promiscuous mating (the pbGWp) and a Poisson distribution of offspring number, that the probability of extinction relative to that for the corresponding ordinary (asexual) Galton-Watson process, tends to a limit as the initial number (i) of parasites increases. Alsmeyer & Rösler (1996) sought a theoretical basis for the numerical result of Daley et al (1986), restricting their consideration to promiscuous mating but with a general offspring distribution, and were able to obtain upper and lower bounds for the ratio of the extinction probabilities. Numerical studies confirmed the earlier observation that the ratio converges rapidly with i .…”
Section: Definition Of Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not a severe constraint, since most mating functions considered in two-sex branching process theory are superadditive (see, e.g. Hull (1982) or Daley et al (1986)).…”
Section: Probability Generating Functionsmentioning
confidence: 99%
“…In particular, it is our purpose to model the probabilistic evolution of populations where females and males coexist and form couples (female-male). Several classes of discrete-time two-sex (bisexual) branching processes have been studied, including the bisexual Galton-Watson process (see Rösler (1996), (2002), Bagley (1986), Bruss (1984), Daley (1968), and Daley et al (1986)); processes with immigration (see González et al (2000), (2001), and Ma and Xing (2006)); in varying environments (see , (2004a)); and processes depending on the number of couples in the population (see Molina et al (2002Molina et al ( ), (2004bMolina et al ( ), (2006, and Xing and Wang (2005)). We refer the reader to Hull (2003) or Haccou et al (2005, pp.…”
Section: Introductionmentioning
confidence: 99%